1996
DOI: 10.1002/(sici)1099-1263(199609)16:5<401::aid-jat364>3.3.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Laundering on Ability of Glove Fabrics to Decrease the Penetration of Organophosphate Insecticides Through in vitro Epidermal Systems

Abstract: Two knit glove fabrics, one of 100% cotton and one of 100% polypropylene, were examined for their capability to decrease the penetration of the organophosphate insecticides (OPs), azinphos-methyl and paraoxon after 4 h at field concentrations (3000 and 15 ppm, respectively) through an in vitro epidermal system (Skin2@, Advanced Tissue Systems, LaJolla, CAI. The glove fabrics were examined under three different conditions of use: new, after they had been abraded and after they had been abraded and then laundere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Out of the fabrics tested, 100% cotton in 13‐cut and 7‐cut displayed the lowest rates of acetyl cholinesterase inhibition through the in vitro system, therefore providing the best protection against the organophosphate pesticides (Keeble, Corell, & Ehrich, 1993). A later study by Keeble, Corell, and Ehrich (1996) used in vitro test systems to study the effect of laundering on permeation properties of fabric and subsequent percutaneous penetration (Keeble, Corell, & Ehrich, 1996). They found that fabric contaminated with azinphos‐methyl in petroleum distillates provided protection regardless of fabric laundering status, whereas fabric contaminated with paraoxon in ethanolic solution displayed decreased protection against percutaneous absorption when the fabric had been laundered (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Out of the fabrics tested, 100% cotton in 13‐cut and 7‐cut displayed the lowest rates of acetyl cholinesterase inhibition through the in vitro system, therefore providing the best protection against the organophosphate pesticides (Keeble, Corell, & Ehrich, 1993). A later study by Keeble, Corell, and Ehrich (1996) used in vitro test systems to study the effect of laundering on permeation properties of fabric and subsequent percutaneous penetration (Keeble, Corell, & Ehrich, 1996). They found that fabric contaminated with azinphos‐methyl in petroleum distillates provided protection regardless of fabric laundering status, whereas fabric contaminated with paraoxon in ethanolic solution displayed decreased protection against percutaneous absorption when the fabric had been laundered (Table 1).…”
Section: Resultsmentioning
confidence: 99%